2020
DOI: 10.1149/1945-7111/aba933
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Morphology of Electro-spun EPAA Coatings on the H2S Sensing Performance of Corresponding Interdigitated Electrodes

Abstract: In this article, the fabrication of interdigitated electrode (denoted by IDE) H 2 S sensor based on electroactive polyamic acid (denoted by EPAA) containing oligoaniline in the main chain is first demonstrated. First step involved the synthesis of aminocapped aniline trimer (denoted by ACAT). Subsequently, the EPAA and correspondent electroactive polyimide (EPI) was prepared by reacting ACAT and 4,4′-(4,4′-isopropylidene-diphenoxy)bis(phthliic anhydride (BSAA), followed by characterization. For the study of ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…The water contact-angle measurements of PUU-AC0, PUU-AC1, and PUU-AC3 were 79.7°, 73.3°, and 72.2°, respectively, indicating their hydrophilic nature. The hydrophilic groups may have developed intermolecular interactions with polar H 2 S gas, thus increasing the response of the sensor [ 27 , 73 ].…”
Section: Response and Sensitivitymentioning
confidence: 99%
See 2 more Smart Citations
“…The water contact-angle measurements of PUU-AC0, PUU-AC1, and PUU-AC3 were 79.7°, 73.3°, and 72.2°, respectively, indicating their hydrophilic nature. The hydrophilic groups may have developed intermolecular interactions with polar H 2 S gas, thus increasing the response of the sensor [ 27 , 73 ].…”
Section: Response and Sensitivitymentioning
confidence: 99%
“…PANI reinforced with various carbon fillers has been used to improve gas-sensing performance [ 21 , 22 , 23 , 24 , 25 , 26 ]. However, considering the poor solubility of PANI, aniline oligomer-based polymers have attracted intensive research interests in the past decade [ 27 ]. In 2005, Zhao et al designed a floating-gate ion-sensitive field-effect transistor that used doped aniline trimer as a sensing material; this transistor could sense up to 70 ppm of NH 3 gas [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The redox property of PANI and its derivative polymers make them applicable for electrochemical sensing [ 9 , 10 , 11 ]. Their doping/dedoping property also expands their useability for gas sensing [ 12 , 13 , 14 ]. The first publication related to H 2 S sensing was reported by Monkman in 1995.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Chao and Wang prepared OAEPs that have remarkable electrochemical and electrochromic behavior [ 34 , 35 ]. In 2020, Yeh et al reported an H 2 S gas sensor based on an electroactive polymer containing aniline trimer in the main chain [ 36 ]. Additionally, Huang et al, prepared a polylactide-based OAEP for tissue engineering [ 37 ].…”
Section: Introductionmentioning
confidence: 99%